1987
DOI: 10.1128/iai.55.2.451-454.1987
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Vibrio cholerae non-O1 protease and soluble hemagglutinin with those of Vibrio cholerae O1

Abstract: Protease and soluble hemagglutinating activities produced by a non-O1 Vibrio cholerae strain isolated from a patient with diarrhea were compared with similar activities produced by V. cholerae 01. The soluble protease activities were indistinguishable in heat stability, immunodiffusion, inhibition by antiserum, and electrophoretic analysis. On the other hand, the soluble hemagglutinating activities of both strains were not completely identical. The hemagglutinating activity of the non-O1 V. chokrae strain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…1). The purified protease was biochemically and physicochemically identical to HA/protease, as previously reported by Booth et al [3] and Honda et al [7]. The hemagglutinin activity of purified protease, however, was not detected as previously reported [15].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…1). The purified protease was biochemically and physicochemically identical to HA/protease, as previously reported by Booth et al [3] and Honda et al [7]. The hemagglutinin activity of purified protease, however, was not detected as previously reported [15].…”
Section: Resultssupporting
confidence: 85%
“…The strains of V. cholerae used in the experiment are listed in Table 1. Protease activity of strains of V. cholerae was checked by a single-diffusion technique in agar gel (0.75%) containing skim milk (1.5%) as a substrate as previously described [7]. A total of 40 strains of V. cholerae were cultured in tryptic soy broth with shaking at 30°C for 20 h. Culture supernatant (20 /zl) obtained after centrifugation (40000 × g, 20 min) was added to wells 3.5 mm in diameter, and the plates were incubated for 12 h at 37°C.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Results presented are representative of at least three independent experiments. Haemagglutinin/protease activity was detected by a minor modification of Blackwell Science Ltd, Molecular Microbiology, 25, 1099-1111 a previously described single-diffusion technique in agar containing 1% skim milk as substrate (Honda et al, 1987).…”
Section: Assaysmentioning
confidence: 99%
“…It also nicks and activates CT and CT-related enterotoxins [24]. Besides the protease activity, HA/P also shows hemagglutinating activity [25,26] on erythrocytes of Balb/c mice, but this activity has not been consistently reproduced [27,28]. Our study showed that NMDCY has a protease activity which is inhibited by metal chelators, but has no hemagglutinating activity on Balb/c mice and chicken erythrocytes.…”
Section: Resultsmentioning
confidence: 73%